Modificações laríngeas e vocais produzidas pelo som vibrante lingual - Schwarz, Karine (2006)
This research had like objective to investigate the vocal and laryngeal effect and sensations that appeared from to the execution of the voiced tongue vibration technique (VTVT) applied in three series of fifteen repetitions, in the maximum time of phonation with habitual tone and intensity, with pauses of thirty seconds of passive rest between each serie. For that, had taken part in the study 24 people, of the female sex, ranging from 25 to 41 years old, without vocal complaints. All those persons were submitted to a perceptive-auditive and acoustic of voice analysis, through the Multi-Dimensional Voice Program (MDVP) - Model 5105 e Multi- Speech - Model 3700, of Kay Elemetrics; and a valuation of the larynx, by means of video laryngostroboscopic exam, before and after the execution of VTVT. The results of the appreciation were analyzed of quantitative and qualitative form, by means of statistic examinations, being compared with the existent bibliography about the subject. The analysis of the results had become evident that it was statistically significant, after the execution of the VTVT: the improvement of the kind of voice; of the focus of vertical resonance; of the vocal quality; the increase of the fundamental frequency; the improvement of the parameters of the spectrographic evaluation, in the Large Band and Narrow Band filters; the maintenance of the parameters of the laryngeal images (glottal closure, constriction of the laryngeal vestibule, amplitude and symmetry of the vibration of the vocal folds); the betterment of the medial constriction of the vestibule, according to the increase of time of the execution of the VTVT; and the predominance of the positive sensations;. The data of this study also had permitted to conclude, that the VTVT presents modifications about the glottal source and about the resonant filter